Citizenship in Name Only: Constructing Meaningful Citizenship through a Recalibration of the Values Attached to Waged Labor - MacGregor, Marion (Disability Studies Quarterly, 2012)
In November 2010 the Toronto Star reported that the newly revamped Canadian citizenship test had led to an unusually high failure rate. Using the generally, although not universally, accepted understanding of citizenship as a set of civil, political and social rights and responsibilities the more meaningful test is how, or whether, we can exercise our citizenship. Closer examination reveals a deeply rooted connection between the ability to exercise social citizenship and participation in waged labor. Denied access to waged labor, as people with disabilities systematically are, undermines a person’s identity as an active citizen and his or her ability to exercise social citizenship. A recalibration of the values associated with waged labor namely, independence, self-reliance and productivity would extend worth and identity to those systemically deprived of both, produce allies amongst historically disadvantaged groups, and benefit broader segments of society many of who grow disenchanted with the current distribution of wealth and power. Key Words: waged labor, productivity, independence, social citizenship, meaningful citizenship